Correlates of access to hand hygiene resources in Ghanaian households: An exploratory analysis of the 2014 demographic and health survey. Issue 8 (August 2020) - Kenney, Paul Lawer; Agboh, Herman Nuake Kofi; Agyemang, Florence Akosua; Dadzie, Seth Sylvester; Duah, Henry Ofori; Agbadi, Pascal
Abstract: Objectives: Handwashing with soap and water remains the most effective public health measure to reduce the risk of infectious diseases, which kill over 2.5 million people annually, mostly children in developing countries. The absence of hand hygiene resources in homes put many at risk of these infectious diseases. In the wake of the outbreak of the COVID-19 pandemic, the World Health Organization (WHO) and governments around the world have stressed the importance of regular handwashing to prevent the spread of the virus. This suggests that research on water, sanitation, and hygiene issues deserve continuous scholarly attention. In Ghana, studies on household's access to hand hygiene resources are few and relatively old. Therefore, this study estimated the proportion of Ghanaian households with access to hand hygiene resources and their associated determinants using data from a recent national survey. Methods: The study used the cross-sectional 2014 Ghana Demographic and Health Surveys dataset. We used STATA-14 to perform data analyses on a weighted sample of 11, 710.06 households. We used complex samples analysis technique to adjust for sample units, stratification and sample weights for both the descriptive statistics and multivariate robust Poisson regression. Results: The result showed that about one fifth of Ghanaian households had access to hand hygiene resources. Households with heads who attained a Middle/JHS/JSS or Secondary/SSS/SHS/Higher level education, those headed by persons having at least 30–44 years, and non-poorest households, and from the Volta region were more likely to have access to hand hygiene resources. Further, households in urban areas, households that spent between 0-30 min to get to a source of water, and households in Eastern and Brong-Ahafo regions were less likely to have access to hand hygiene resources. Conclusion: This study identified key socioeconomic and demographic correlates of a household's access to hand hygiene resources in Ghana. In the interim, the government and development partners can provide hand hygiene resources to households with limited or no access. For the long term, we recommend that the government should implement measures and policies that facilitate citizens' economic independence and their attainment of higher formal education. Abstract : Public health; Health disparity; Health promotion; Human geography; Social geography; Hand hygiene; Soap; Water; Sanitation; Demographic and health surveys; Ghana.